KEMAMPUAN PEMAHAMAN KONSEP DERET TAK HINGGA MENGGUNAKAN AUGMENTED REALITY PADA APLIKASI GEOGEBRA DI UNIVERSITAS NEGERI MEDAN - Nasution, Helina Qatrunnada; Rahmah, Khalida; Syafitri, Nazwa Mutia; Simanullang, Michael Christian (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study was to determine the ability to understand the concept of infinite series using Augmented Reality in the Geogebra application at Medan State University. The research method used in this research is a descriptive qualitative method. The instruments for collecting data in this research were interviews and analytical skills tests. Three students from the mathematics education study program class PSPM 23 B, Medan State University, were taken as samples for interviews and analytical skills tests. The test is carried out on infinite series material. Next, analysis of all data was carried out using the following steps: data reduction stage, data presentation stage, and conclusions. The research results show that: 1. Students with a visual learning style tend to understand concepts more easily through graphic displays and simulations provided by AR. They can identify patterns and shapes of infinite series better, but some of them have difficulty generalizing the concept and connecting it to broader theory, 2. Students with an auditory learning style rely more on verbal explanations and discussions to understand the material. Although they can grasp concepts through communication-based learning strategies, they are less than optimal in understanding the direct visualizations presented by AR. This shows that the use of AR needs to be supported with clearer narratives or guidance for students with this learning style. 3. Students with a kinesthetic learning style show the most significant increase in understanding. With AR, they can interact directly with the concepts being studied, see shape changes in real-time, and understand the growth patterns of infinite series more concretely. This proves that interactive technology-based learning is very effective for students who rely more on direct experience in understanding the material.